2018
DOI: 10.1111/myc.12823
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity of Pneumocystis jirovecii from a cluster of cases of pneumonia in renal transplant patients: Cross‐sectional study

Abstract: Pneumocystis jirovecii can cause severe potentially life-threatening pneumonia (PCP) in kidney transplant patients. Prophylaxis of patients against PCP in this setting is usually performed during 6 months after transplantation. The aim of this study is to describe the molecular epidemiology of a cluster of PCP in renal transplant recipients in Brazil. Renal transplant patients who developed PCP between May and December 2011 had their formalin-fixed paraffin-embedded (FFPE) lung biopsy samples analysed. Pneumoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 51 publications
1
12
1
Order By: Relevance
“…Furthermore, besides identifying the risk factors of PJP, it is necessary for kidney transplantation recipients to obtain effective prophylaxis against PJP, especially those with high risks of PJP, such as patient with acute rejection (AR), 6 certain genotypes of Pneumocystis jirovecii 7,8 or severe lymphopenia 9 after surgery. Trimethoprim‐sulfamethoxazole (TMP‐SMX) is considered to be the first choice for PJP prophylaxis, and the incidence of PJP after renal transplantation was significantly reduced by prophylactic use of TMP‐SMX.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, besides identifying the risk factors of PJP, it is necessary for kidney transplantation recipients to obtain effective prophylaxis against PJP, especially those with high risks of PJP, such as patient with acute rejection (AR), 6 certain genotypes of Pneumocystis jirovecii 7,8 or severe lymphopenia 9 after surgery. Trimethoprim‐sulfamethoxazole (TMP‐SMX) is considered to be the first choice for PJP prophylaxis, and the incidence of PJP after renal transplantation was significantly reduced by prophylactic use of TMP‐SMX.…”
Section: Introductionmentioning
confidence: 99%
“…In Brazil, a pioneering study in PcP patients showed an absence of DHPS gene mutations. In contrast, a recent report described clusters of P. jirovecii with DHPS mutations among immunosuppressed patients following renal transplantation [32,33]. Among Colombian patients with PcP or PjC, DHPS mutations in respiratory samples were detected at a low rate [34].…”
Section: Developing Countriesmentioning
confidence: 86%
“…A prospective epidemiological study of PcP patients from three European cities showed nosocomial transmission of P. jirovecii that had mutations in the DHPS gene that could explain the high proportion of mutations in patients without exposure to sulfa drugs [19]. Additionally, possible nosocomial transmission has been investigated in other locations [33,87,88]. In France, longitudinal screening of patients with PcP and PjC suggested that circulation of Pneumocystis exists within hospitals [87], and more recently, the presence of Pneumocystis harboring DHPS mutant genotypes in the environment of a bronchoscopy unit has been described in Spain [88].…”
Section: Transmissionmentioning
confidence: 99%
“…Guarro et al identified a strain of Fusarium verticillioides from blood culture and F. solani from a skin biopsy, both from the same HIV-positive patient [77]. The DNA extracted from FFPE samples allowed Ricci et al to describe the molecular epidemiology of a cluster of Pneumocystis jirovecii pneumonia in renal transplant recipients, uncovering that 4 out 11 patients were infected by more than one genotype [78]. Ponzio et al have identified patients infected with various molecular siblings of Cryptococcus neoformans, such as VNI and VNII, isolated from infected patients' cerebrospinal fluid or blood [79].…”
Section: Discussionmentioning
confidence: 99%